Estimation of withdrawal interval recommendations following administration of fenbendazole medicated feed to ring-necked pheasants (Phasianus colchicus) - Carreño Gútiez, Marta; Mercer, Melissa A.; Martínez-López, Beatriz; Griffith, Ronald W.; Wetzlich, Scott; Tell, Lisa A. (Frontiers in Veterinary Science, 2024)
Prescribing fenbendazole medicated feed for pheasants in the USA is considered extra-label drug use, and the Animal Medicinal Drug Use Clarification Act requires that a safe estimated withdrawal interval (WDI) be applied following administration to this minor food-producing species. This study sought to determine the pharmacokinetic and residue depletion profile for fenbendazole and its major metabolites in pheasants' (n=32) liver and muscle tissue samples in order to estimate a WDI for pheasants following fenbendazole administration as an oral medicated feed at 100 ppm for 7 consecutive days. Fenbendazole, fenbendazole sulfoxide, and fenbendazole sulfone in pheasant liver and muscle samples were analyzed using HPLC-UV. Liver and muscle sample concentrations were used to estimate WDIs using FDA, European Medicines Agency (EMA), and half-life multiplication methods with US poultry tolerances, EMA maximum residue limits, and the analytical limit of detection (LOD; 0.004 ppm) as the residue limits. Terminal elimination half-lives were estimated by noncompartmental analysis using a naïve pooled data approach and were 14.4 h for liver, 13.2 h for thigh muscle, and 14.1 h for pectoral muscle. The maximum estimated withdrawal interval was 153 h (7 days) for fenbendazole sulfone for pectoral muscle using the FDA tolerance method (95 % confidence interval for the 99 th percentile of the population), and the LOD as the residue limit.